2009
DOI: 10.1159/000232933
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Extracorporeal Circuit in the Trapping and Degranulation of Platelets

Abstract: Background: Although platelet (PLT) activation and degranulation are well-known phenomena during hemodialysis (HD), controversies still exist about their nature and origin. Methods: PLT characteristics [PLT numbers, mean PLT volume (MPV), PLT distribution width (PDW), PLT large cell ratio (p-LCR), immature PLT fraction] and activation status [CD62p expression, platelet factor 4 (PF4) and β-thromboglobulin (BTG) plasma levels] were estimated in 19 patients before and during HD. Blood was sampled from both the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…Shear stress in the extracorporeal circuit may be an important trigger in sP-Selectin-mediated platelet aggregation. The finding in our study of a significant intra-dialytic reduction in MPV, PDW, and P-LCR, as demonstrated previously by Gritters-van den Oever et al, may be also be in line with platelet activation during the HD procedure [14]. MPV decreased during HD treatment and hence the MPV derived parameters P-LCR and PDW decreased as well.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Shear stress in the extracorporeal circuit may be an important trigger in sP-Selectin-mediated platelet aggregation. The finding in our study of a significant intra-dialytic reduction in MPV, PDW, and P-LCR, as demonstrated previously by Gritters-van den Oever et al, may be also be in line with platelet activation during the HD procedure [14]. MPV decreased during HD treatment and hence the MPV derived parameters P-LCR and PDW decreased as well.…”
Section: Discussionsupporting
confidence: 90%
“…Given the effects of hemodialysis (HD) on platelet activation, and due to the highly dynamic blood-ESL interaction, it can be hypothesized that HD may also have acute effects on the ESL [14,15,16]. However, it is unknown whether ESL damage is exacerbated even during the HD treatment in patients with end-stage renal disease (ESRD).…”
Section: Introductionmentioning
confidence: 99%
“…Docci et al [11] found a significant platelet loss during cuprophan dialysis, but not with polyacrylonitrile membranes. However, Gritters-van den Oever et al [12] reported that platelet numbers markedly dropped after hemodialysis with low-flux PS dialyzers. As the drop over the extracorporeal circuit at the first passage amounted to approximately 15%, the combined activation and number of platelets suggest that a considerable number of activated platelets stick to the extracorporeal circuit, most probably the dialyzer membrane directly after the start of hemodialysis [13] .…”
Section: Discussionmentioning
confidence: 99%
“…During HD treatment, blood constituents interact with the foreign surfaces within the extracorporeal circuit (ECC), including the wall of blood lines, the artificial dialyzer membrane and mechanical forces of the roller pump. Within the ECC endothelium is lacking and activation of PLTs and biomarkers inducing activation of coagulation are released by mechanical triggers [23]. In order to prevent clotting in the ECC during HD, a bolus of low molecular weight heparin or unfractionated heparin is supplied at the start of each HD session.…”
Section: Discussionmentioning
confidence: 99%
“…Increase of PLT activation and procoagulant activity is demonstrated in HD patients [24,25]. PLTs are activated within the ECC, as detected by increase in the expression of CD62p and release of β-tromboglobulin (β-TG) within the ECC [23]. PLT activation is associated with exposure of phosphatidylserine on the PLT exterior.…”
Section: Discussionmentioning
confidence: 99%